BA 111 - Introduction to Practical Accounting I - Linn Benton Virtual College (2018)
This course covers the fundamental principles of double-entry accounting, use of the general journal and general ledger, simple financial statements, the accounting cycle, control of cash, and an introduction to payroll accounting, purchases and sales.